Effect of annealing to the mechanical Properties and microstructure of stainless steel foil for sensor of large automobile - Aziz, Abdul; Putera, Alfi Eko (Faculty of Engineering, Universitas Sultan Ageng Tirtayasa, 2024)
The SUS 316 thin metal foils have widely used in the field of industries, such a electronic, industries. The aim of this research wants to clarify the effect of annealing and quench temper to the mechanical properties of SUS 316 thin metal foils. The SUS 316 thin metal foil (TMF) after annealing and quench temper treatment at 900 oC for 3 hours were studied by uniaxial tensile and microstructure analysis. The SEM-EBSD investigation used for microstructure analysis. The result of this research shown that the difference of uniaxial tensile test occur in SUS 316L with different grain size (Dg) such as 1,0 um until 9,0 um. Martensitic phase transformation (MPT) occur in SUS 316 TMF as shown in SEM-EBSD result. The microstructure change indicated by the change of grain misorientation (GMO) in SUS 316 TMF fine grains and coarse grain.